Be open to failure : Open innovation failure in dynamic environments - Zahoor, Nadia; Adomako, Samuel (Elsevier, 2023)
Despite the considerable efforts made to investigate the factors that could potentially influence open innovation (OI), very little is understood about the impact of environmental factors such as dynamism. In addition, the question relating to the relationship between environmental factors and OI remains unresolved. Further, the conditions under which this relationship is more or less pronounced are also little understood. With our study, we examined these gaps through data collected from 209 emerging market small and medium enterprises (ESMEs) operating in the United Arab Emirates (UAE). Our analyses show that environmental dynamism negatively influences OI and that this nexus is mediated by organizational learning culture. In addition, we found that the mediation effect of organizational learning culture is moderated by relational trust, in that it is improved at high levels of relational trust. Finally, we found that the organizational learning-OI nexus is moderated by firm size and industry type. These findings extend our knowledge of the role played by micro-environmental factors in OI activities.
Keywords: Environmental dynamism; Organizational learning culture; Open innovation; Relational trust; SMEs; Emerging markets; small and medium-sized enterprises